Performance of Porous Asphalt Mixtures Using De-oiled Bleaching Earth (DBE) Filler With University Of New Hampshire Stormwater Center (UNHSC) Gradation - Yafi Argyan Setiyanda Farrel; Boedi Rahardjo; Pranoto Pranoto (EPI International Journal of Engineering, 2025)
Porous asphalt is an asphalt mixture designed with open-graded composite material and serves to drain water on the road surface into the pore of the mixture. The coarse aggregate composition that dominates the porous asphalt mixture makes it have low stability, in this research, DBE was used as a filler replacement to improve the performance of the mixture. This study aims to determine the performance of porous asphalt mixture using DBE filler with UNHSC gradation. Variations of DBE filler content used were 0%, 25%, 50%, 75%, and 100% by weight of filler. Test specimens with DBE filler were made using optimum asphalt content (KAO), with tests including Marshall test, binder drain down, permeability, and cantabro loss. The results showed that the performance of porous asphalt mixtures with DBE fillers obtained stability and VIM values decreased and flow values increased. In the permeability test, the highest value was 0.214 cm/s at 0% DBE, the highest cantabro loss value was 28.07% at 100% DBE, and the highest binder drain-down value was 0.24% at 0% DBE. The results of the research can conclude that the use of DBE as a filler can reduce the performance of porous asphalt mixtures.